Making history : Josephus and historical method - Rodgers, Zuleika (Supplements to the Journal for the study of Judaism, 2007)
The encounter between interpretation and history in the writings of Josephus provides the conceptual framework for this collection of essays. In particular, the question of historical method, both ancient and modern, is explored from a variety of perspectives.